Temporal water quality response in an urban river: a case study in peninsular Malaysia - VishnuRadhan, Renjith; Zainudin, Zaki; Sreekanth, G. B.; Dhiman, Ravinder; Salleh, Md Noor; Vethamony, P. (Springer Berlin Heidelberg, 2017)
Ambient water quality is a prerequisite for the health and self-purification capacity of riverine ecosystems. To understand the general water quality situation, the time series data of selected water quality parameters were analyzed in an urban river in Peninsular Malaysia. In this regard, the stations were selected from the main stem of the river as well as from the side channel. The stations located at the main stem of the river are less polluted than that in the side channel. Water Quality Index scores indicated that the side channel station is the most polluted, breaching the Class IV water quality criteria threshold during the monitoring period, followed by stations at the river mouth and the main channel. The effect of immediate anthropogenic waste input is also evident at the side channel station. The Organic Pollution Index of side channel station is (14.99) ~3 times higher than at stations at river mouth (4.11) and ~6 times higher than at the main channel (2.57). The two-way ANOVA showed significant difference among different stations. Further, the factor analysis on water quality parameters yielded two significant factors. They discriminated the stations into two groups. The land-use land cover classification of the study area shows that the region near the sampling sites is dominated by urban settlements (33.23 %) and this can contribute significantly to the deterioration of ambient river water quality. The present study estimated the water quality condition and response in the river and the study can be an immediate yardstick for base lining river water quality, and a basis for future water quality modeling studies in the region